Malignant bowel obstruction in advanced ovarian cancer. (March 2017) - Dean, Emma; Khoja, Leila; Clamp, Andrew; Jayson, Gordon C; Goonetilleke, Dilly; Conway, Alicia M; Hasan, Jurjees
Aim: Malignant bowel obstruction (MBO) in ovarian cancer is poorly understood.Methods: This retrospective cohort study analyzed 129 patients with ovarian cancer and MBO.Results: At presentation, 69 (53%) had platinum-resistant, 37 (29%) platinum-sensitive and 23 (18%) chemotherapy-naive disease. In patients receiving chemotherapy following the MBO episode, median overall survival (OS) was 107 days for chemotherapy-naive patients compared with 83 and 86 for platinum-sensitive or platinum-resistant patients (p = 0.98). OS was inferior for best supportive care (45 days) compared with chemotherapy (152 days) or surgery (124 days; p < 0.001). The Manchester Bowel Obstruction Score using Eastern Cooperative Oncology Group and obstruction level discriminated patients by median OS of 181 days (neither) versus 98 days (one) versus 42 days (both; p < 0.01).Conclusion: The Manchester Bowel Obstruction Score may aide treatment stratification.